2006
DOI: 10.1124/mol.106.025775
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen Recruits Spinal p42/p44 MAPKs and GH/IGF-1 Receptors to Produce Analgesia via the Serotonergic System

Abstract: The mechanism of action of acetaminophen is currently widely discussed. Direct inhibition of cyclooxygenase isoforms remains the commonly advanced hypothesis. We combined behavioral studies with molecular techniques to investigate the mechanism of action of acetaminophen in a model of tonic pain in rats. We show that acetaminophen indirectly stimulates spinal 5-hydroxytryptamine (5-HT) 1A receptors in the formalin test, thereby increasing transcript and protein levels of low-affinity neurotrophin receptor, ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Serotonin (also known as 5-hydroxytryptamine, 5-HT) exerts effects via several subtypes of its cognate receptor, and its localization in axon termini places these subtypes in prime location for the modulation of pain, transmission and processing (42,43). Previous studies have reported that acetaminophen may exert antinociceptive effect through increasing the levels of serotonin released from serotonergic neurons in the brainstem, known as central mediation (42,43). Furthermore, results have suggested that acetaminophen acts directly on the opioid receptor or cannabinoid (CB) receptor, or indirectly by increasing levels of the endogenous ligands including opioid or anandamide (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin (also known as 5-hydroxytryptamine, 5-HT) exerts effects via several subtypes of its cognate receptor, and its localization in axon termini places these subtypes in prime location for the modulation of pain, transmission and processing (42,43). Previous studies have reported that acetaminophen may exert antinociceptive effect through increasing the levels of serotonin released from serotonergic neurons in the brainstem, known as central mediation (42,43). Furthermore, results have suggested that acetaminophen acts directly on the opioid receptor or cannabinoid (CB) receptor, or indirectly by increasing levels of the endogenous ligands including opioid or anandamide (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism underlying acetaminophen-induced analgesia via the serotonergic system was recently studied [68]. Acetaminophen modulated the expression of four genes in the lumbar enlargement of the rat spinal cord following the formalin test, but not in naive rats.…”
Section: The Serotonergic System and Its Relation To Non-opioidsmentioning
confidence: 99%
“…After 2 days, the cells were collected and hRFPL1 expression was assessed by semiquantitative end-point PCR as previously described 43 or by real-time PCR as described below.…”
Section: Methodsmentioning
confidence: 99%